Konsep Diri, Pola Asuh Orang Tua Demokratis Dan Kepercayaan Diri Siswa - Nirwana, * (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2013)
Abstract. The purpose of research was to find correlations between self concept and democratic parental with students’ self confidence. The subject of research was 82 students of SMK NEGERI I Mojokerto, consists of 55 boys and 27 girls. The data was collected with used self concept scale, democratic parent educated and self confidence. The collected data was analyzed by regression analyzed and continued partial correlation. The result showed; there were significance relationship between self concept and democracy parental with self confidence of students. Also, the result showed positive correlation between either self concept or democratic parental with students’ self confidence. Keywords: Self concept, democratic parental, student’ self-confidence.